Bridging gaps in InsurTech and e-commerce integration: Insights from Saudi Arabia - Laith Khrais (Insurance Markets and Companies)
The integration of insurance technology with e-commerce in Saudi Arabia is a key driver of financial and technological advancement, aligning with Vision 2030, the national strategy for economic diversification and digital transformation. This study examines the technological factors influencing this integration, assessing both enablers and barriers, including application programming interfaces, artificial intelligence, real-time risk assessment, cybersecurity, outdated infrastructure, and regulatory alignment. A quantitative approach was employed, gathering data from 253 professionals in Saudi Arabia’s insurance and e-commerce sectors, including financial managers handling underwriting and investment, compliance officers ensuring regulatory compliance, information technology specialists overseeing system integration and cybersecurity, and policymakers shaping industry regulations. Structural equation modeling revealed that application programming interfaces (β = 0.78, p = 0.020), artificial intelligence (β = 0.70, p = 0.025), and real-time risk assessment (β = 0.62, p = 0.030) significantly facilitate integration, while cybersecurity vulnerabilities (β = 0.57, p = 0.035), outdated infrastructure (β = 0.54, p = 0.040), and regulatory misalignment (β = 0.57, p = 0.035) pose major barriers. Additionally, government incentives (β = 0.51, p = 0.040) and workforce expertise (β = 0.49, p = 0.035) influence adoption outcomes. The findings highlight the need for regulatory harmonization, enhanced cybersecurity, financial support, and workforce training to facilitate seamless integration and ensure the long-term sustainability of insurance technology in Saudi Arabia’s evolving digital economy.